Three-dimensional atom probe analysis of boron segregation at austenite grain boundary in a low carbon steel - Effects of boundary misorientation and quenching temperature. (September 2018) - Miyamoto, Goro; Goto, Ai; Takayama, Naoki; Furuhara, Tadashi
Abstract: Segregation of boron at random austenite grain boundaries with known misorientation angle in a boron-added low carbon steel quenched from austenite state at different temperatures was investigated quantitatively using three-dimensional atom probe. Boron segregation is reduced at low angle boundaries or low quenching temperatures. The latter result indicates that non-equilibrium boron segregation plays an important role and is enhanced at higher quenching temperature due to more excess vacancies and longer diffusion distance during quenching from higher temperature. Graphical abstract: Unlabelled Image